Detection of antimicrobial producing Staphylococcus from migratory birds: Potential role in nasotracheal microbiota modulation - Fernández-Fernández, Rosa; Abdullahi, Idris Nasir; González-Azcona, Carmen; Ulloa, Adriana; Martínez, Agustí; García-Vela, Sara; Höfle, Ursula; Zarazaga, Myriam; Lozano, Carmen; Torres, Carmen (Frontiers in Microbiology, 2023)
AA collection of 259 staphylococci of 13 different species (212 coagulase-negative [CoNS] and 47 coagulase-positive [CoPS]) recovered from nasotracheal samples of 87 healthy nestling white storks was tested by the spot-on-lawn method for antimicrobial-activity (AA) against 14 indicator bacteria. Nine of these isolates (3.5%; 7 CoNS and 2 CoPS) showed AA against at least one indicator bacteria and were considered antimicrobial-producing (AP) isolates. The AP isolates showed AA only for Gram-positive bacteria. Moreover, extracts of AP isolates were obtained (cell-free-supernatants [CFS] both crude and concentrated and butanol extracts) and tested against the 14 indicator bacteria. Three of these AP isolates (S. hominis X3764, S. sciuri X4000 and S. chromogenes X4620) revealed AA on all extract conditions; the other 4 AP isolates only showed activity in extracts after concentration; the remaining 2 AP isolates did not show AA in any of extract conditions. For the microbiota modulation analysis, the AP isolates were tested for: a) intra-sample AA, against all Gram-positive bacteria recovered in the same stork nasotracheal sample; b) inter-sample AA against a selection of representative Gram-positive bacteria of the nasotracheal microbiota of all the storks (30 isolates of 29 different species and 9 genera). In this respect, 3 of the 9 AP-isolates revealed intra-sample AA. Moreover, it highlights the potent inter-sample AA of the X3764 isolate inhibiting 73% of the 29 representative Gram-positive species of the nasotracheal stork microbiota population. In addition, the proteinaceous nature of the antimicrobial compound of two selected AP isolates (X3764 and X4000, both with the highest AA) was verified by an enzymatic susceptibility test. The presence of genes encoding lantibiotic-like antimicrobial peptides was detected by PCR and sequencing in the 9 AP isolates. In conclusion, these results show that nasotracheal staphylococci of healthy storks, and especially CoNS, produce antimicrobial substances that could be important in the modulations of their nasal microbiota.